(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Factors like age,sex, literacy level, marital status are some important attributes that play amajor role in travel process. After analysing those attributes mentioned above,it was found that their profiles are more or less similar to general touristsin India. For instance, age profile, sex, marriage status can be seen followingthe established pattern of general tourists. In terms of education, a healthytrend is that a good chunk of them are well educated and possess graduationdegree or above, whereas, illiterates are generally very negligible in numbers.This, in turn, is reflected in their employment status as well with 60% of respondentsstating to be in some form of jobs. The private sector emerges to be largestemployer followed by public sector. Interestingly, as many as one-third of thedomestic respondents are found engaged in some form of self-employmentactivities. Again, among those employed, nearly 33% of domestic ones work atofficer/executive levels, but, corresponding proportion for foreign tourists isabout 50%. It further shows the proportion of support staff more in the sampleof domestic tourists. Indeed, better employment profile was reflected in theirincome status, with over 34% of households reportedly earn more than Rs 40000/-per month and another 22% earn in the range of Rs 20001 to Rs 40000/-. However,households of Problems and Prospects of Accessible Tourism in India 133 foreignrespondents earning more than one lakh rupees in a month are almost half of thesample. The income pattern thus emerges is a clear indication of theirpurchasing power as well the market potential.